A co-simulation approach for straddle monorail vehicle–bridge interaction subjected to nonlinear excitation. (June 2023) - Zhou, Junyong; Huang, Cheng; Deng, Jiangdong; Zhang, Junping; Zhang, Lingkai
Highlights: Most existing simulation approaches for VBI systems cannot consider structural nonlinearity and external nonlinear excitations. Co-simulation approach using MATLAB and ANSYS is proposed to analyze nonlinear responses of straddle monorail VBI systems. VBI responses of straddle monorail systems in the literature validate the accuracy of the proposed co-simulation approach. Favorable computational efficiency for the co-simulation approach with structural nonlinearity and nonlinear excitations. Abstract: Straddle monorail systems, a lightweight rail transit mode, are being increasingly used for developing infrastructures in medium-sized cities. Vehicle–bridge interaction (VBI) is a critical issue in the design of straddle monorail systems. However, existing straddle monorail VBI studies have not simultaneously considered nonlinear excitations, structural nonlinearities, and bridge alignment defects. Therefore, this study proposes a co-simulation approach that combines MATLAB and ANSYS software packages to analyze the dynamic responses of a straddle monorail VBI system. The equations of motion of the monorail train are formulated following D'Alembert's principle and are solved by self-programming on the MATLAB platform. A finite element model of the bridge is established and solved using the ANSYS programming. The bridge and vehicle subsystems are coupled through global iteration with the exchange of wheel–rail contact forces calculated using MATLAB and bridge responses calculated using ANSYS. The co-simulation approach is validated by the dynamic responses of the monorail train and bridge reported in the relevant literature. To demonstrate further the effectiveness and high efficiency of the proposed approach, the dynamic responses of the VBI system with a monorail train crossing a three-span continuous rigid-frame prestressed concrete-girder bridge are analyzed, and three investigated cases of sole earthquake, sole moving-train, and combined earthquake and moving-train excitations are compared. These results demonstrated that the proposed co-simulation approach can provide an effective tool for nonlinear dynamic responses of straddle monorail VBI systems subjected to nonlinear excitation and other nonlinear-coupled dynamic issues.